2023
DOI: 10.1038/s41467-023-36892-4
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibition triggers ICAM1-driven immune response and sensitizes LKB1 mutant lung cancer to immunotherapy

Abstract: Liver kinase B1 (LKB1) mutation is prevalent and a driver of resistance to immune checkpoint blockade (ICB) therapy for lung adenocarcinoma. Here leveraging single cell RNA sequencing data, we demonstrate that trafficking and adhesion process of activated T cells are defected in genetically engineered Kras-driven mouse model with Lkb1 conditional knockout. LKB1 mutant cancer cells result in marked suppression of intercellular adhesion molecule-1 (ICAM1). Ectopic expression of Icam1 in Lkb1-deficient tumor incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…RB carries several phosphorylation sites as substrates for cyclin A-CDK2, cyclin B-CDK1, cyclin D-CDK4/6, and cyclin E-CDK2. 1,44,45 Based on the of METTL3 and AURKB knockdown on the cell cycle and the expression of CCND1, we hypothesized that CCND1 was the regulator responsible for phosphorylating RB. As expected, the p-RB was decreased significantly in goat granulosa cells transfected with siCCND1, and serval studies have reported the similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RB carries several phosphorylation sites as substrates for cyclin A-CDK2, cyclin B-CDK1, cyclin D-CDK4/6, and cyclin E-CDK2. 1,44,45 Based on the of METTL3 and AURKB knockdown on the cell cycle and the expression of CCND1, we hypothesized that CCND1 was the regulator responsible for phosphorylating RB. As expected, the p-RB was decreased significantly in goat granulosa cells transfected with siCCND1, and serval studies have reported the similar results.…”
Section: Discussionmentioning
confidence: 99%
“…RB carries several phosphorylation sites as substrates for cyclin A‐CDK2, cyclin B‐CDK1, cyclin D‐CDK4/6, and cyclin E‐CDK2 1,44,45 . Based on the different effects of METTL3 and AURKB knockdown on the cell cycle and the expression of CCND1, we hypothesized that CCND1 was the regulator responsible for phosphorylating RB.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in SPOP degradation inhibited ubiquitination-mediated PD-L1 degradation, PD-L1 expression was increased, and the effect of immunotherapy was further improved ( Zhang et al, 2018 ; Zeng et al, 2021 ). Preclinical studies have shown that CDK4/6 inhibitors dephosphorylate RB, inhibit the activation of the transcriptional repressor complex RB-E2F, and downregulate the expression of the DNA methyltransferase DNMT1, enhancing the activation of cytotoxic cells and improving the antigen presentation of tumor cells ( Goel et al, 2017 ; Schaer et al, 2018 ; Bai et al, 2023 ). CDK4/6 inhibitors activated endogenous retroviral elements, leading to increased dsDNA expression, promoting IFN expression, activating the body’s innate and adaptive anti-tumor immune response, and greatly improving the efficacy of immunotherapy ( Tong et al, 2022 ).…”
Section: Preclinical and Clinical Trials Of Ddr Inhibitors In Combina...mentioning
confidence: 99%
“…Moreover, the expression of immunosuppressive cells (Tregs, MDSC) in TME was further reduced through the inhibition of NFAT family proteins and their target genes by CDK4/6 inhibitors ( Yu et al, 2019 ; Zhang et al, 2020 ). Combining palbociclib with an anti-PD-1 antibody also promotes NK cell infiltration and CD107a expression in NK cells, increased infiltration of active cytotoxic cells, and a series of events that synergistically reverse the immunosuppressive TME, increasing the sensitivity of tumor cells to immunotherapy ( Bai et al, 2023 ). CDK4/6 inhibitors also lower the apoptotic threshold of tumor cells by inhibiting the phosphorylation of P73, leading to nuclear translocation of P73, and inducing activation of DR5, allowing tumor cells to be readily affected by multiple therapeutic modalities ( Tong et al, 2022 ).…”
Section: Preclinical and Clinical Trials Of Ddr Inhibitors In Combina...mentioning
confidence: 99%
“…Previous studies have shown that human endogenous retrovirus (HERV) elements from the LTR12C subfamily derepressed by DNMTi or DNMTi-HDACi mainly contribute to immunogenic TE-chimeric transcripts [21,22]. Moreover, inhibition of DNMT induces expression of TEs that can form double-stranded RNA (dsRNA) to activate type I/III interferon response [24][25][26][27]. Derepressed TE-derived dsRNA induces viral mimicry that can make cancer cells sensitive to immune therapy [25,28].…”
Section: Introductionmentioning
confidence: 99%